2010
DOI: 10.1016/j.stem.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Myosin Contractility Is Responsible for the Reduced Viability of Dissociated Human Embryonic Stem Cells

Abstract: SUMMARY Human ES cells are the pluripotent precursor of the three embryonic germ layers. Human ES cells exhibit basal-apical polarity, junctional complexes, integrin-dependent matrix adhesion, and E-cadherin-dependent cell-cell adhesion, all characteristics shared by the epiblast epithelium of the intact mammalian embryo. After disruption of epithelial structures, programmed cell death is commonly observed. If individualized human ES cells are prevented from reattaching and forming colonies, their viability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
289
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(310 citation statements)
references
References 42 publications
17
289
2
2
Order By: Relevance
“…Previous studies showed that actomyosin hyperactivation led to dissociation-induced apoptosis of embryonic and induced-pluripotent stem cells [9][10][11] . Although it is still controversial whether this type of cell death belongs to anoikis, the consensus was that the excessive actin-myosin contraction caused by loss of E-cadherindependent intercellular contact is critical for dissociation-induced death of embryonic or induced-pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies showed that actomyosin hyperactivation led to dissociation-induced apoptosis of embryonic and induced-pluripotent stem cells [9][10][11] . Although it is still controversial whether this type of cell death belongs to anoikis, the consensus was that the excessive actin-myosin contraction caused by loss of E-cadherindependent intercellular contact is critical for dissociation-induced death of embryonic or induced-pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 98%
“…These results together suggest that Akt activity is essential for Myh9 inhibition to promote the survival and pluripotency of Lgr5 þ stem cells. Myh9-mediated actin-myosin contraction has been suggested to be involved in dissociation-induced apoptosis of embryonic and induced-pluripotent stem cells [9][10][11] . We then tested whether disruption of actin filament polymerization could also improve the survival of isolated crypts.…”
Section: Dissociation-induced Myh9 Expression Restricts Crypt Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of ROCKI and/or ROCKII was performed using Dharmacon SMART pool ON-TARGETplus ROCK1 siRNA (L-003536-00-0005) and ON-TARGETplus ROCK2 siRNA (L-004610-00-0005), which were already demonstrated to be specifi c in hESC ( 47 ). Control for transfection was done using ON-TARGETplus NonTargeting Pool (D-001810-10-05).…”
Section: Sirna Knockdown Of Rockmentioning
confidence: 99%
“…Two concurrent studies revealed that hESC dissociation (breakdown of E-cadherinmediated interaction) led to long-lasting apoptotic cellular contraction due to myosin hyperactivation in a Rho/ ROCK-dependent manner. Inhibition of ROCK or myosin heavy chain ATPase (by blebbistatin) diminishes actomyosin contraction and rescues the dissociated hESCs from apoptosis [17,18].…”
Section: Discovery-based Chemical Approachesmentioning
confidence: 99%